THU0584 Clinical Characteristics of Sarcoid Arthropathy. (15th July 2016) - Kobak, S.; Sever, F.; Usluer, O.; Goksel, T.; Orman, M.
Abstract : Background: Sarcoidosis is known as a Th1-mediated disease which can mimic many primary rheumatologic diseases or can sometimes co-exist with them. Clinical characteristics of sarcoid arthropathy are not well described as only referral-based studies have been reported. Objectives: The aim of this study were to evaluate the incidence and clinical characteristics of sarcoid arthropathy. Methods: We used an inception cohort of sarcoidosis patients seen between July 2011 and August 2015. A total of 114 (32 male) sarcoidosis patients, who admitted to our clinic were included in the study. Clinical, demographical, laboratory, radiological and histological data of these patients obtained during 4-year follow-up and treatment period were compiled and analyzed. Results: The mean patient age was 48.1 years (20–82 years), and the mean disease duration was 40.5 months (1–300 months). Sarcoid arthritis was observed in 71 (62.3%), and arthralgia in 106 (92.9%) patients. Out of the 71 patients with arthritis, 61 (85.9%) had involvement of ankle, 7 (9.8%) knee, two (2.8%) wrist, MCP and PIP joints, and one (1.4%) had shoulder periarthritis. Oligoarthritis (two to four joints) was the most common pattern followed by monoarthritis and polyarthritis. When the correlation between clinical findings were considered, erythema nodosum and arthritis and female gender were found to be correlated (p=0.03, p=0.001, respectively). Again in patients with arthritis, even higher levels of CRP/ESR as well as ANA and RF positivity were observed (p=0.03, p=0.01, p=0.01 and p=0.02, respectively). Eleven patients had another rheumatic pathology concurrent with sarcoidosis (1SjS, 3RA, 1Still disease, 1 Scleroderma, 4AS, 1FMF). Conclusions: Inflammatory arthritis occurs in a majority of patients with sarcoidosis. Acute arthritis with bilateral ankles involvement was the most common pattern of sarcoid arthropathy. Sarcoidosis can mimic many primary rheumatic disease and/or may coexist. Sarcoidosis should be considered not only as a mimicker but also as a Th1-mediated primary rheumatologic pathology. Disclosure of Interest: None declared